Dynamic self-fulfilling fire sales - Paymon Khorrami; Fernando Mendo (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2025)
Why do fire sales occur if many risks are hedgeable? We study a version of Brunnermeier and Sannikov (2014) in which all fundamental risks can be hedged frictionlessly. Our analysis shows that fire sales are inherently self-fulfilling. Fundamental shocks can never cause fire sales, and an efficient, safe equilibrium exists. On the other hand, there exists an equilibrium in which agents coordinate fire sales on non-fundamental shocks. A simple refinement based on vanishingly-small perceived fundamental risk eliminates the safe equilibrium and selects the fire sale equilibrium as the unique outcome.
Keywords: E00; E44; G01; 330; financial frictions; fire sales; self-fulfilling equilibria; financial crises; hedging